1987
DOI: 10.3354/meps035129
|View full text |Cite
|
Sign up to set email alerts
|

Time series of particulate and dissolved lipid classes during spring phytoplankton blooms in Bedford Basin, a marine inlet

Abstract: The Chromarod-Iatroscan TLC/FID system was used to measure h p~d classes in the dissolved and particulate fractions of seawater samples taken dunng spnng blooms In Bedford Basln, a small inlet in eastern Canada. Polar hpids were the major dissolved lipids present during the bloon~s. Dissolved l i p~d t~m e series indicate decreased phytoplankton exudation and increased bacterial uptake of lipid classes at the t~m e of the chlorophyll maximum. There is evidence to suggest algal uptake of dissolved phospholip~ds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 13 publications
3
57
0
Order By: Relevance
“…The lipids were extracted from the suspended particulate matter samples using chloroform-methanol 2 : l (v/v). The lipid classes in the extracts were separated on silica gel coated Chromarod-S111 using 4 different solvent systems and then measured in a n Iatroscan MK V (Parrish 1987). The first solvent system was hexane/diethyl ether/formic acid (99 : 1 : 0.05 by vol.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lipids were extracted from the suspended particulate matter samples using chloroform-methanol 2 : l (v/v). The lipid classes in the extracts were separated on silica gel coated Chromarod-S111 using 4 different solvent systems and then measured in a n Iatroscan MK V (Parrish 1987). The first solvent system was hexane/diethyl ether/formic acid (99 : 1 : 0.05 by vol.).…”
Section: Methodsmentioning
confidence: 99%
“…In a comparison between the total triacylglycerol concentration determined by GC on the non-polar column and the total 3000 triacylglycerol concentration determined using the Iatroscan, the 2 totals were corre-2500 lated (r = 0.63, p < 0.02, n = 15) and there was no significant difference between the E means (p = 0.08). However, on average the Zm GC gave a lower total than the Iatroscan, : 151-164, 1995 Scotia from March to August (Parrish 1987, Goutx 1988, Parrish et al 1992b. Total lipid concentrations (Table 1) were 13 to 64 % of the averages of 116 + 27 and 400 * 54 pg 1-' measured in the vicinity of Halifax after the spring bloom (Parrish 1987, Goutx 1988) and 63 to 89% of the total measured in Ship Harbour, a mussel aquaculture site, in August 1989 (Parrish et al 1992b).…”
mentioning
confidence: 99%
“…Crashes can result from a number of factors including nutrient exhaustion, grazing, sedimentation, or viral lysis and remains a fundamentally poorly understood process in all microalgae [36,37]. Environmental studies have shown that once chlorophyll levels begin to decrease (signaling the beginning of the end of the bloom), triacylglycerol (TAG) content increases [38,39]. Translating that into a biofuels production scenario, TAG accumulation precedes cell death and thus crashing would not necessarily be detrimental to production.…”
Section: The Relevance Of Natural Productivity To Biofuels Productionmentioning
confidence: 99%
“…Parrish (1987) hypothesized that dissolved lipids he measured in Bedford Basin (Canada) were exuded by phytoplankton during the spring bloom. There has been some work on extracellular lipid production by marine diatoms grown in continuous culture (Parrish & Wangersky, 1987;Lombardi & Wangersky, 1991).…”
Section: Fatty Acids and Lipidsmentioning
confidence: 99%